A Comparative Analysis of Patient Satisfaction and Cosmetic Outcomes after Breast Reconstruction through BREAST-Q and the Judgment of Medical Panels: Does it Reflect Well in Terms of Aesthetics in Korean Patients? - Choi, Woo Jung; Song, Woo Jin; Kang, Sang Gue (Archives of Plastic Surgery, 2022)
Background Currently, the BREAST-Q can effectively measure patient's satisfaction on the quality of life from the patient's perspective in relation to different type of breast reconstruction. However, evaluation of patient satisfaction and cosmetic outcomes in breast reconstruction may have potential to led bias.Methods To maximize the benefits of using BREAST-Q to evaluate clinical outcome, we performed comparative study focused on the correlation between postoperative BREAST-Q and cosmetic outcomes assessed by medical professionals. For the current analysis, we used three postoperative BREAST-Q scales (satisfaction with breast, psychosocial well-being, and sexual well-being). The Ten-Point Scale by Visser et al was applied to provide reproducible grading of the postoperative cosmetic outcomes of the breast. The system includes six subscales that measured overall aesthetic outcome, volume, shape, symmetry, scarring, and nipple-areolar complex. The photographic assessments were made by five medical professionals who were shown photographs on a computer screen in a random order. Obtained data were stored in Excel and evaluated by Spearman's correlations using SPSS Statistics.Results We enrolled 92 women in this study, 10 did not respond to all scales of postoperative BREAST-Q, the remaining 82 women had undergone breast reconstruction. The correlation between BREAST-Q score and aesthetic score measured by Ten-Point Scale for the three BREAST-Q scales all show positive values in Spearman's correlation coefficient.Conclusion A significant correlation without any bias observed was found between the patient's satisfaction measured by BREAST-Q after breast reconstruction and the medical expert's aesthetic evaluation.
Keywords: BREAST-Q; breast reconstruction; patient-reported outcome